A new framework of firm-level innovation capability: A propensity–ability perspective. Issue 2 (April 2023) - Daronco, Everaldo Luis; Silva, Diego S.; Seibel, Martina Konzen; Cortimiglia, Marcelo Nogueira
Abstract: One of the critical topics in contemporary innovation management literature concerns what constitutes innovation capability (IC) at the firm level. There have been many attempts to conceptualize and operationalize this capability. Still, they either fail to discriminate the elements that characterize IC or to present consistent, comparable elements across distinct models or frameworks. This paper reports the results of a systematic approach to formulate a firm-level IC framework. To do so, the authors conducted an extensive systematic literature review, screened 19, 589 papers, and analyzed in detail 186 documents that directly address empirical or theoretical elements of IC. The researchers cross-analyzed these papers for direct and indirect references to ICs (and related concepts, such as innovation orientation, innovation competence, and innovativeness) and generated thematic categories. We drew on a hybrid approach moving between inductive and deductive coding and theme development. We adopted an ex-ante theoretical perspective of the propensity/ability axis built upon the willingness–ability approach and the dynamic capability lens. The proposed synthetizing framework is coherent with Teece's (2014) ordinary and dynamic capabilities. It comprises two sets of elements: on one hand, structural and contextual antecedents that characterize an organization's propensity toward innovation and, on the other hand, actions and resource-related capacities that act as causal mechanisms that, articulated within functions—sensing, seizing, and transforming—constitute the ability to generate innovation.